Qibla Determination through the Sun Transit over Ka’ba - bin Mohamed, Azhari; Zambri Zainuddin, Mohd. (Malaysian Journal of Science, 2003)
Astronomical computations show that each year the sun appears exactly overhead Ka’ba on May 28 and July 16. This occurs when the declination of the sun is equivalent to the geographical latitude of Ka’ba. Facing the sun precisely during that moment in time will give the correct direction of the qibla. These twice-a-year phenomena provide excellent opportunities to the Muslims around half the globe to check and confirm their direction of qibla. Solar observations at two locations, namely Telok Kemang and Bukit Malawati on July 16, 2000 have been carried out. The objective of the study is to compare the observed directions of qibla from the two locations during the sun transit over Ka’ba with their corresponding computed values. The observed and computed values of the direction of qibla show a difference of between 3 arcminutes at Telok Kemang and 7 arcminutes in Bukit Malawati.